Exploring the role of microglia in cortical spreading depression in neurological disease. Issue 4 (April 2017) - Shibata, Mamoru; Suzuki, Norihiro
Microglia play a pivotal role in innate immunity in the brain. During development, they mature from myeloerythroid progenitor cells in the yolk sac and colonize the brain to establish a resident population of tissue macrophages. In the postnatal brain, they exert phagocytosis and induce inflammatory response against invading pathogens. Microglia also act as guardians of brain homeostasis by surveying the microenvironment using motile processes. Cortical spreading depression (CSD) is a slowly propagating (2–5 mm/min) wave of rapid, near-complete depolarization of neurons and astrocytes followed by a period of electrical suppression of a distinct population of cortical neurons. Not only has CSD been implicated in brain migraine aura, but CSD-like events have also been detected in stroke and traumatic injury. CSD causes a considerable perturbation of the ionic environment in the brain, which may be readily detected by microglia. Although CSD is known to activate microglia, the role of microglial activation in CSD-related neurological disorders remains poorly understood. In this article, we first provide an overview of microglial development and the multiple functions of microglia. Then, we review existing data on the relationship between microglia and CSD and discuss the relevance of CSD-induced microglial activation in neurological disease.